2006
DOI: 10.1146/annurev.med.57.061804.084505
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in Thrombotic Thrombocytopenic Purpura

Abstract: Recent advances have demonstrated that thrombotic thrombocytopenic purpura (TTP), characterized by widespread thrombosis in the arterioles and capillaries, is caused by deficiency of a circulating zinc metalloprotease ADAMTS13. Two types of TTP are recognized: Autoimmune TTP caused by inhibitory antibodies of ADAMTS13 and hereditary TTP in association with genetic mutations of the ADAMTS13 gene. This article reviews the characteristic and function of ADAMTS13, the mechanism by which ADAMTS13 deficiency may cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 70 publications
1
73
0
4
Order By: Relevance
“…More than 65 mutations, including nonsense, missense, frame-shifting insertion or deletion and splicing mutations, have been detected in patients with hereditary TTP [99][100][101][102][103]. The mutations affect the process of protease synthesis, activity, or more commonly, secretion.…”
Section: Hereditary Thrombotic Thrombocytopenic Purpuramentioning
confidence: 99%
“…More than 65 mutations, including nonsense, missense, frame-shifting insertion or deletion and splicing mutations, have been detected in patients with hereditary TTP [99][100][101][102][103]. The mutations affect the process of protease synthesis, activity, or more commonly, secretion.…”
Section: Hereditary Thrombotic Thrombocytopenic Purpuramentioning
confidence: 99%
“…[4,5,10] In the absence of ADAMTS 13 or its decreased activity, there is an environment conducive to excessive link between Von Willebrand Factor and platelets, causing greater adhesion, aggregation and microthrombosis. [10][11] In autoimmune form is striking the presence of anti -AD-AMTS13 autoantibodies, primarily of the IgG class, whereas in the idiopathic form, the main factor of susceptibility is the presence of HLA-DRB1 * 11 in Caucasians. [12] In Upshaw -Schulman syndrome, occurs mutations in the ADAMTS13 gene, over 50 different mutations have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…[12] In Upshaw -Schulman syndrome, occurs mutations in the ADAMTS13 gene, over 50 different mutations have been identified. [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Ultra-large VWF (Ͼ 20 million kDa) is the most thrombogenic form of VWF and is cleaved to smaller, less thrombogenic forms by the multidomain structured 185 kDa metalloprotease a disintegrin-like and metalloprotease with thrombospondin type I repeats-13 (ADAMTS13) in the plasma. 3 In humans, qualitative or quantitative abnormalities of the VWF protein cause the VWF disease, an inherited common bleeding disorder, whereas lack of functional AD-AMTS13 results in thrombotic thrombocytopenic purpura, which is characterized by the formation of thrombi in arterioles and capillaries. 3,4 Studies in mice demonstrated that lack of VWF was highly protective in a model of ischemic stroke and improved the neurologic outcome, 5,6 whereas ADAMTS13 deficiency aggravated the neurologic damage.…”
Section: Markus Bender University Hospital Würzburgmentioning
confidence: 99%